Efficacy of cinnamon supplementation on glycolipid metabolism in T2DM diabetes: A meta-analysis and systematic review - Zhou, Qian; Lei, Xingxing; Fu, Shunlian; Li, Zinan; Chen, Yiding; Long, Cong; Li, Suwen; Chen, Qiu (Frontiers in Physiology, 2022)
ABSTACT Background Cinnamon is a spice that is used in cooking and by some in large quantities as a complement with hypoglycemic and lipid-lowering properties. The potential pharmacological mechanisms underlying the efficacy by which cinnamon and their active ingredients indicated anti-diabetic properties have not been adequately identified. The current meta-analysis aims to systematically review the potential pharmacological mechanisms underlying the hypoglycemic and lipid-lowering efficacy of Cinnamon administration and summarize clinical recommendations of Cinnamon and its active ingredients. Method Relevant randomized clinical trials (RCTs) were identified through a literature search that spanned the years January 2005 to April 2022. Retrieve electronic databases including Web of Science, PubMed, Embase, Medline, and the Cochrane Library. To obtain standardized mean differences (SMDs), continuous outcomes were pooled and 95 percent confidence intervals (CIs) were provided. Categorical outcomes were aggregated to calculate relative risks (RRs) and were accompanied by 95% CIs. Heterogeneity was measured using the Cochrane Q-test and I2 statistics, with a P < 0.05 considered as substantial heterogeneity. Subgroup analyses and sensitivity analyses were performed to identify the origins of heterogeneity. Publication bias was retrieved by means of a funnel-plot analysis and Egger’s test. Data were analyzed using revman (V.5.3) and stata (V.15) softwares. Results These 16 RCTs included a total of 1020 patients who were followed for a duration ranging from forty days to four months. According to the current meta-analysis, Glycolipid levels in diabetic individuals who received cinnamon were considerably were significantly improved as compared to those who got placebo (All P< 0.05). The adverse effect was only detected in one patient. Conclusion These findings imply that cinnamon has a significant influence on lipid and glucose metabolism regulation. An even more pronounced effect was observed in patients with HbA1c of 8%. The results of this study suggested that cinnamon may be utilized as Hypoglycemic and lipid-lowering supplement in clinic in the future, and that its safety could be assured.